Bipolar electrochemistry in synergy with electrophoresis: electric field-driven electrosynthesis of anisotropic polymeric materials. Issue 92 (20th October 2020) - Shida, Naoki; Inagi, Shinsuke
Abstract : The synergistic effect of bipolar electrochemistry and electrophoresis enables facile access to various anisotropic functional materials. Abstract : Bipolar electrochemistry, which refers to an electrochemical system at a wireless electrode driven under an applied electric field, has been recognized as not only a simple subset of conventional electrosynthetic systems but a reaction system with a highly unique nature. One notable feature is the presence of the electrophoretic effect due to the low electrolyte concentration. The electrophoresis enhances the mass transfer of ionic species in a specific direction, thus enabling the efficient construction of anisotropic materials. In this Feature Article, we summarized our recent reports on the fabrication of anisotropic conductive polymer fibers and films via bipolar electrochemistry in synergy with the electrophoretic effect.